Wastewater Disposal Systems and Types of Wastewater - Sarvarjon Botirjon ugli Abduraimov (International Journal on Orange Technologies, 2021)
The water disposal system is currently understood as a complex of engineering structures and measures for receiving wastewater, removing it outside a settlement, railway station or industrial enterprise in order to supply it to special facilities for cleaning, neutralization and further reuse or, as an exception, for discharge into a water body.